Whole genome and exome sequencing identify NDUFV2 mutations as a new cause of progressive cavitating leukoencephalopathy. Issue 4 (2nd April 2021) - Liu, Zhimei; Zhang, Li; Ren, Changhong; Xu, Manting; Li, Shufang; Ban, Rui; Wu, Ye; Chen, Ling; Sun, Suzhen; Elstner, Matthias; Shimura, Masaru; Ogawa-Tominaga, Minako; et al.
Abstract : Background: Progressive cavitating leukoencephalopathy (PCL) is thought to result from mutations in nuclear genes affecting mitochondrial function and energy metabolism. To date, mutations in two subunits of complex I, NDUFS1 and NDUFV1, have been reported to be related to PCL. Methods: Patients underwent clinical examinations, brain MRI, skin biopsy and muscle biopsy. Whole-genome or whole-exome sequencing was performed on the index patients from two unrelated families with PCL. The effects of the mutations were examined through complementation of the NDUFV2 mutation by cDNA expression. Results: The common clinical features of the patients in this study were recurring episodes of acute or subacute developmental regression that appeared in the first years of life, followed by gradual remissions and prolonged periods of stability. MRI showed leukoencephalopathy with multiple cavities. Three novel NDUFV2 missense mutations were identified in these families. Complex I deficiency was confirmed in affected individuals' fibroblasts and a muscle biopsy. Functional and structural analyses revealed that these mutations affect the structural stability and function of the NDUFV2 protein, indicating that defective NDUFV2 function is responsible for the phenotypes in these individuals. Conclusions: Here, we report the clinical presentations, neuroimaging and molecular and functional analyses of novel mutations in NDUFV2 in two sibling pairs of two Chinese families presenting with PCL. We hereby expand the knowledge on the clinical phenotypes associated with mutations in NDUFV2 and the genotypes causative for PCL.